Partial oxidation reforming of simulated biogas in gliding arc discharge system - Patipat Thanompongchart (2018)
Plasma assisted, partial oxidation reforming of biogas is considered to be a promising technology to produce synthesis gas. In this work, a 0.1 kW gliding arc plasma reformer was employed to investigate the effects of biogas composition and oxygen availability on CH 4 and CO 2 conversions, as well as the product distribution. Air was used in the partial oxidation of biogas. The results showed that at low CH 4 /O 2 ratio or high oxygen availability, increasing CH 4 content appeared to show higher H 2 yield and CH 4 conversion. Increasing CH4/O 2 ratio adversely affected H 2 and CO yields, and CH4 conversion. Optimum condition was found at CH 4 /CO 2 of 90:10 and CH 4 /O 2 of 1.2 for the maximum CH 4 conversion and H 2 yield of 45.7 and 25.3%, respectively.